Normothermic Perfusion in Organ Preservation and Evaluation. Promising Future in Kidney Transplantation. - Mora-Ruiz, Guillermo; Ochoa, Ignacio; Moreo, Pedro (Jornada de Jóvenes Investigadores del I3A, 2025)
Kidney transplantation remains the best treatment for end-stage renal disease. Normothermic Machine Perfusion (NMP) could be a useful tool that could solve the problems that arise from the high demand for organs and their quality, providing a suitable platform for investigating treatments that would not be possible in vivo.